2016
DOI: 10.14814/phy2.12713
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training improves vascular function in adolescents with type 2 diabetes

Abstract: The impact of exercise training on vascular health in adolescents with type 2 diabetes has not been previously studied. We hypothesized that exercise training would improve micro‐ and macrovascular health in adolescents with type 2 diabetes. Thirteen adolescents (13–21 years, 10F) with type 2 diabetes were recruited from Princess Margaret Hospital. Participants were randomized to receive either an exercise program along with standard clinical care (n = 8) or standard care alone (n = 5). Those in the interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 41 publications
1
47
1
Order By: Relevance
“…Exercise training in middle-aged subjects improved forearm resistance vessel endothelial function (65) and NO bioavailability (281). Exercise training also improves endothelial function and/or increases the contribution of NO to basal tone in subjects with cardiovascular risk including hypertension (131), T2DM (193,223), obesity (202) and hypercholesterolemia (183,316) and in subjects with coronary artery disease (114, 315) and heart failure (115,116,192,194 plasma levels were found in postmenopausal women (227) and hypertensive subjects (123).…”
Section: Resistance Arteriesmentioning
confidence: 99%
“…Exercise training in middle-aged subjects improved forearm resistance vessel endothelial function (65) and NO bioavailability (281). Exercise training also improves endothelial function and/or increases the contribution of NO to basal tone in subjects with cardiovascular risk including hypertension (131), T2DM (193,223), obesity (202) and hypercholesterolemia (183,316) and in subjects with coronary artery disease (114, 315) and heart failure (115,116,192,194 plasma levels were found in postmenopausal women (227) and hypertensive subjects (123).…”
Section: Resistance Arteriesmentioning
confidence: 99%
“…At the same time, endothelial progenitors can be mobilized by noninvasive "technique"-yes, with nutraceuticals: Stem-Kine complex augmented hemopoietic and endothelial progenitors (CD133+ and KDR-1/CD34+) just the next day after beginning of administration [266]. Moreover, moderate exercises actually improve vascular function in patients with type 2 diabetes [267], thus giving us confidence in elaborating more natural approaches to solve the problems of vascular health and disease. Now, we have to finalize and feel obliged to offer some advice, so we will try.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…For instance, our group has already reported that low‐intensity aerobic exercise training, performed at least three times per week, increased endothelial‐dependent capillary reactivity in patients with type 1 diabetes and coronary artery disease . Prior research has also demonstrated that exercise training improved endothelial function in adolescents with type 2 diabetes and chronic heart failure, compared to sedentary patients who received only standard clinical care. Although our results of vascular function seem to be aligned to prior research in other cohorts, we cannot assure whether there is any peculiarity in HIV‐infected patients compared to other cohorts of sedentary vs active individuals, as comparison between them is lacking.…”
Section: Discussionmentioning
confidence: 96%